Status and Challenges on Design and Implementation of Camber Morphing Mechanisms - Tuba Majid; Bruce W. Jo (International Journal of Aerospace Engineering)
This paper presents state-of-the-art technologies of camber morphing mechanisms from the perspectives of design and implementation. Wing morphing technologies are aimed at making the aircraft more energy or aerodynamically efficient during flight by actively adjusting the wing shape, but their mechanism designs and implementation aspects are often overlooked from practical sense in many technical articles. Thus, it is of our interest that we thoroughly investigate morphing mechanisms and their nature of design principles and methodologies from the implementation and test flight aspects, navigate the trends, and evaluate progress for researchers’ methodology selection that possibly turns to design and build stages. This paper categorizes the camber morphing mechanisms from a wide collection of literature on morphing wings and their mechanisms, and the defined classifications are based on mechanism’s design features and synthesis methodology, i.e., by the tools and methods used to solve the design problem. The categories are (1) structure-based, (2) material-based, and (3) hybrid. Most of the structure-based camber morphing mechanisms have distinctive structural features; however, the material-based camber morphing mechanisms make use of material properties and tools to enhance the elastic nature of its structures. Lastly, the hybrid morphing mechanisms are a combination of both the aforementioned categories. In summary, this review provides researchers in the field of morphing mechanisms and wings with choices of materials, actuators, internal and external structure design for wings, and overarching process and design methodologies for implementation with futuristic and practical aspects of flight performance and applications. Moreover, through this critical review of morphing mechanism, selective design criteria for appropriate morphing mechanisms are discussed.